Carbonate and TOC content and isotopic composition from DSDP/ODP sites along the Sunda margin - Brian M House; Gray E Bebout; David R Hilton (PANGAEA, 2019)
The subduction and release of carbon at convergent margins is a primary mechanism by which tectonic processes influence atmospheric pCO2, but the balance between the amount of C subducting and the CO2 flux from volcanic arcs remains poorly constrained. Estimating CO2 recycling efficiency in complex regions like the Sunda margin, Indonesia is particularly difficult due to the lateral variability in sediment thickness, composition, and fraction subducted. We present a new approach for estimating sedimentary C flux that combines high-precision C content and isotope measurements with a regional sediment and unit thickness model we generated from seismic profiles to more accurately extrapolate compositional measurements from sediment core sites to and along the margin. Our results suggest that the subducting sedimentary C flux is up to an order of magnitude less than previous estimates and cannot alone account for the volume of CO2 released along the volcanic arc. Together, this and the isotopic composition of subducting sedimentary C, suggest an additional isotopically-heavy C source contributes to the released CO2. Carbon from carbonate - likely from subducted altered oceanic crust and the overriding plate - can account for the discrepancy between both amount and isotopic composition of sedimentary C influx and volcanic CO2 efflux. These results highlight the importance of considering the full range of subduction zone processes operating at individual margins in order to better understand the cycling of C and other elements. Similar scrutiny should be applied in the evaluation of C subduction inputs to other subduction margins to improve global estimates of tectonic C cycling.
Supplement to: House, BM et al. (2019): Carbon cycling at the Sunda margin, Indonesia: A regional study with global implications. Geology, 47(5), 483-486, https://doi.org/10.1130/G45830.1